Pyrene substituted terfluorenes: special influence of non-conjugated pyrene group on thermal and electroluminescent properties. (November 2013) - Tang, C; Xu, H; Liu, F; Liu, X-D; Xia, Y-J; Wang, X-L; Huang, W
Abstract : To systematically explore the special influence of non-conjugated pyrene substitution, three pyrene substituted terfluorenes (P1TF, P2TF and P3TF), with non-conjugated pyrene rings at C9 of the fluorene moieties, were designed and synthesised by Suzuki coupling reaction. P1TF was a stable amorphous material with high T g of 195°C. Although there were additional peaks on absorption spectra that originated from the non-conjugated pyrene groups, the photoluminescence spectra showed no obvious difference from emission of standard conjugated fluorenes. The three materials not only showed improved highest occupied molecular orbitals compared with phenyl substituted terfluorene but also maintained the high photoluminescence efficiency of the terfluorenes. After systematic comparison, quantum chemical calculations showed that the one non-conjugated pyrene group in terfluorenes significantly affected the thermal stability, stable conformation and highest occupied molecular orbitals of the compounds. Last, the primary device using P1TF as emitter [ITO/TCTA (8 nm)/P1TF (30 nm)/BCP (45 nm)/Mg–Ag] showed a blue light emitting with maximum brightness of maximum luminance of 7300 cd m −2 and maximum efficiency of 1·68 cd A −1 .